Diversity of Functional Soil Microbes in Manures and Its Effect on Organic Mustard Green (Brassica juncea) Production - Kurniawati, Ari; Melati, Maya; Aziz, Sandra Arifin; Purwono, Purwono (Department of Agronomy and Horticulture, IPB University, 2019)
The application of organic fertilizer, especially manures, for crop production has long-term effects for soil nutrients availability and improvement of soil structure. The improvement of soil properties involves interactions of various types of microorganism in the soil. The research aimed to study the effects of different types of manures on the diversity of functional soil microbes and its effects on organic green mustard production. The experiment was conducted at IPB organic research field, Cikarawang, Darmaga, Bogor, from April to June 2015. The experiment used a randomized complete block design with two factors; the first factor was types of manure, i.e. chicken, cow, and goat manures; the second factor was manure rates, i.e. 0 and 10 ton.ha-1, so there were six treatments in total, replicated three times. The results showed that chicken manure application resulted in a higher mustard green yield and soil-P content than application of goat manure. The addition 10 ton.ha-1 of manures increased C-organic, N, K, and C/N ratio in soil significantly, but mustard green production was not affected. The diversity of microbe population of the soil treated with all types of manures was high. The addition 10 ton.ha-1 of manures decreased the total number of microbes, but increased the number of cellulose-degrading microbes. The population of cellulose-degrading and phosphate-solubilizing microbes in the soil applied with cow manure was higher than those applied with the other manures.